EFFECT OF WEIGHT LOSS ON CARDIOMETABOLIC RISK FACTORS IN PATIENTS OF CLINICAL AND SUBCLINICAL HYPOTHYROIDISM PRESENTING TO FAMILY PRACTICE (The Research of Medical Science Review, 2025)
Hypothyroidism, both clinical and subclinical, have been linked with cardiometabolic risk, including obesity, insulin resistance, dyslipidemia, and hypertension. In this article, efficacy of weight loss in cardiometabolic factors in both clinical and subclinical hypothyroidism in a family practice setting is determined. 88 subjects (44 with clinical and 44 with subclinical hypothyroidism) underwent a 6-month (May 2024 to October 2024) guided weight loss intervention. Outcomes included significant improvement in body mass index (BMI), fasting blood glucose, lipid profile, and blood pressure, and it can therefore be argued that weight loss is a significant intervention in countering cardiometabolic risks in such cases.